Stereoselective quenching of cedryl carbocation in epicedrol biosynthesis - Shinde, Sandip S.; Navale, Govinda R.; Said, Madhukar S.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2016)
Epicedrol synthase catalyzes the cyclization of achiral diphosphate substrate, (E,E)-farnesyldiphosphate (FPP) into epicedrol. GC-MS analysis of assay extracts obtained by incubating FPP with epicedrol synthase in 21.6 at % H2(18)O buffer showed the molecular ion of 224 for epicedrol. The labeled oxygen study presented here unambiguously demonstrates that the hydroxyl group of the epicedrol synthase enzymatic product, epicedrol, is derived from a water molecule, not from the phosphate moiety of the FPP. (C) 2016 Elsevier Ltd. All rights reserved.

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2019)
A sesquiterpene epicedrol cyclase mechanism was elucidated based on the gas chromatography coupled to electron impact mass spectrometry fragmentation data of deuterated (H-2) epicedrol analogues. The chemo-enzymatic method was applied for the specific synthesis of 8-position labelled farnesyl pyrophosphate and epicedrol. EI-MS fragmentation ions compared with non-labelled and isotopic mass shift fragments suggest that the H-2 of C6 migrates to the C7 position during the cyclization mechanism.

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis (Retraction of Vol 9, Pg 28258, 2019) - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2020)
Retraction of `Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis' by Madhukar S. Said et al., RSC Adv., 2019, 9, 28258-28261.